Organic polymer carbon source, preparation method thereof, positive electrode material and secondary battery
By adopting a preparation method of organic polymer carbon source, the problems of uneven coating carbon and inconsistent particle growth in lithium iron phosphate are solved, more uniform carbon coating and more stable particle growth are achieved, and the positive electrode material is improved stability and electrochemical properties.
Patent Information
- Application Number
- CN202411668499.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
In the preparation of existing lithium iron phosphate, there are problems such as uneven coating carbon, inconsistent particle growth, and large fluctuations in compaction density and electrical properties.
A method for preparing an organic polymer carbon source, which includes mixing alcohols and ether monomers containing unsaturated double bonds with water, preparing a mixture of benzene ring monomers, reducing agents and water, and phosphonic acids A mixture of monomer, chain transfer agent and water is reacted by initiator, coupling agent, etc. to prepare an organic polymer carbon source with excellent dispersion and coating properties.
Effectively solve the problems of uneven carbon coating, inconsistent particle growth, and large fluctuations in compaction density and electrical properties in lithium iron phosphate, and achieve the technical effect of uniform carbon coating and good particle growth consistency, which improves the positive electrode material Batch stability and electrochemical properties.
Smart Images

Figure CN119463054A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an organic polymer carbon source and a preparation method thereof, a positive electrode material and a secondary battery. Background Art
[0002] As a commonly used cathode material for lithium-ion batteries, the electrochemical performance of lithium iron phosphate (LiFePO4) can be improved in many ways, one of which is to dope or coat carbon sources. The selection of carbon sources is crucial to improving the conductivity and cycle performance of lithium iron phosphate.
[0003] In the preparation research of lithium iron phosphate, technicians often fail to pay enough attention to the significant impact of the proportion of each component on the performance of its finished product. For example, the dispersant and the carbon source are added separately. This practice leads to differences in the mechanism of action, resulting in large differences in the dispersion effect and the uniformity of carbon coating, which ultimately affects the stability of the finished product, manifested as poor stability of the finished product. In addition, carbon thermal reduction is a common method for preparing lithium iron phosphate. This method mainly uses carbon materials to reduce the high-valent state of iron (such as trivalent iron) to divalent iron at high temperature, and at the same time realizes the coating of carbon on the surface of lithium iron phosphate particles to enhance the conductivity of the material. However, the following problems exist in the process of preparing lithium iron phosphate by carbon thermal reduction: a single type of carbon source, uneven coating carbon due to performance limitations, inconsistent particle growth, and large fluctuations in compaction density and electrical properties. In fact, the selection of raw material ratios and the mixing process are directly related to the stability of the sintering temperature, and any fluctuations may seriously affect the controllability of the reaction conditions. The consequences may include inconsistent carbon content in the finished product, a wide range of particle size distribution, and uneven electrical properties, which are key factors that restrict battery performance. Therefore, improving the batch stability of lithium iron phosphate cathode materials is crucial to promoting the development of power battery technology and new energy vehicles. Summary of the invention
[0004] In view of the technical problems existing in the background technology, the present application provides an organic polymer carbon source and its preparation method, a positive electrode material and a secondary battery, aiming to solve the technical problems of uneven carbon coating and inconsistent particle growth in the existing lithium iron phosphate preparation, which lead to unstable compaction density and electrochemical performance.
[0005] In a first aspect, the present invention provides a method for preparing an organic polymer carbon source, comprising the following steps: Mixing alcohol and ether monomers containing unsaturated double bonds with water to obtain a base material; Mixing a benzene ring monomer, a reducing agent and water to obtain a first mixture; mixing a phosphonic acid monomer, a chain transfer agent and water to obtain a second mixture; An initiator, a first mixture, a second mixture and a coupling agent are added to the base material to obtain an organic polymer carbon source through reaction.
[0006] In the technical scheme of the embodiment of the present application, alcohol and ether monomers containing unsaturated double bonds are mixed to form a base material; thereafter, the first mixture and the second mixture are prepared respectively; after the initiator, the first mixture, the second mixture, the coupling agent and the initiator are added to the base material, because the concentration of the ether monomers in the base material is the highest, the alcohol and ether monomers with unsaturated double bonds in the base material will first undergo polymerization reaction to obtain a polymerization product; the benzene ring monomers and the phosphonic acid monomers are subjected to a capping reaction at the end group under the condition of the coupling agent and the initiator; the product of the capping reaction and the polymerization product together constitute the above-mentioned organic polymer carbon source. Among them, the double bond participates in the reaction process, while the alcohol hydroxyl group, the ether group, the phosphonic acid group and the benzene ring structure do not participate in the reaction, and thus are retained.
[0007] Understandably, in the present application, the organic polymer carbon source has alcoholic hydroxyl groups, and the excellent hydrophilicity of the alcoholic hydroxyl groups makes the prepared organic polymer carbon source have good water solubility; at the same time, the alcoholic hydroxyl groups have adsorption and complexing capabilities. When the organic polymer carbon source is applied to the preparation of lithium iron phosphate, the alcoholic hydroxyl groups carried by the organic polymer carbon source can not only effectively disperse the agglomerated particles produced in the sand milling and spraying processes, but also can precisely control the particle size, morphology and distribution range of the prepared lithium iron phosphate. In addition, during the sintering stage in the preparation process of lithium iron phosphate, the alcoholic hydroxyl groups carried by the organic polymer carbon source can also guide the growth behavior of lithium iron phosphate, thereby optimizing the structure and performance of the prepared lithium iron phosphate.
[0008] Furthermore, the organic polymer carbon source also has a benzene ring structure, an ether group and a phosphonic acid group, wherein the benzene ring structure is helpful for dispersion, and the ether group has good water solubility and dispersibility. Therefore, when the organic polymer carbon source is applied to the preparation of lithium iron phosphate, during the process of drying and sintering to achieve carbon coating, better coating and dispersion of the carbon layer can be achieved. In particular, in the present application, the benzene ring structure is easy to directly carbonize at high temperature, and can provide an efficient conductive carbon network. The phosphonic acid group has strong adsorption, and combined with the efficient bridging effect of the coupling agent, the carbon coating structure can be further optimized.
[0009] In some embodiments, the molar ratio of alcohols and ether monomers containing unsaturated double bonds to water is (2.5-3.5): (0.1-0.3): (10-20); and / or, in the step of preparing the first mixture, the molar ratio of the benzene ring monomer, the reducing agent and water is (0.05-0.40): (0.001-0.005): (5-10); and / or, in the step of preparing the second mixture, the molar ratio of the phosphonic acid monomer, the chain transfer agent and water is (0.01-0.20): (0.01-0.02): (5-10).
[0010] In this embodiment, by setting the molar ratio of the unsaturated double bond alcohol and ether monomers to water contained in the base material to (2.5-3.5): (0.1-0.3): (10-20), the molar ratio of the benzene ring monomer, the reducing agent and the water contained in the first mixture is set to (0.05-0.40): (0.001-0.005): (5-10), and at the same time, the molar ratio of the phosphonic acid monomer, the chain transfer agent and the water contained in the second mixture is set to (0.01-0.20): (0.01-0.02): (5-10), the prepared organic polymer carbon source has better performance, is less likely to cause excessive waste of raw materials, and is conducive to controlling production costs.
[0011] In some embodiments, the molar ratio of the benzene ring monomer in the first mixture, the phosphonic acid monomer in the second mixture and the ether monomer in the base material is (0.05~0.50):(0.01~0.20):(0.1~0.3); and / or, the molar ratio of the initiator, the benzene ring monomer in the first mixture and the coupling agent is (0.10~0.20):(0.05~0.50):(0.01~0.03).
[0012] In this embodiment, if the content of phosphonic acid monomers in the second mixture is too low, the generated organic polymer carbon source contains too few phosphonic acid groups. In the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the adsorption effect between the phosphonic acid groups and the lithium iron phosphate is weak, resulting in low adhesion of the organic polymer carbon source and poor adhesion of the coating layer. If the content of phosphonic acid monomers in the second mixture is too high, the generated organic polymer carbon source contains too many phosphonic acid groups. In the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the adsorption effect between the phosphonic acid groups and the lithium iron phosphate is strong, resulting in local aggregation of the organic polymer carbon source and uneven thickness of the coating layer.
[0013] Furthermore, if the content of benzene ring monomers in the first mixture is too low, the benzene ring structure contained in the generated organic polymer carbon source will also be too small. In the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the dispersibility of the organic polymer carbon source in the solution will decrease, and agglomeration will easily occur, resulting in uneven thickness of the carbon coating layer; and if the content of benzene ring monomers is too high, the benzene ring structure contained in the generated organic polymer carbon source will be too large, resulting in increased hydrophobicity of the organic polymer carbon source. In the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the organic polymer carbon source is difficult to fully disperse in the solution, making the subsequent carbon coating process difficult.
[0014] Furthermore, the initiator is used to regulate the polymerization reaction rate and will indirectly affect the molecular weight of the organic polymer carbon source. If the initiator is too little, the number of free radicals generated will be too little, thereby slowing down the polymerization reaction rate, prolonging the polymerization reaction time, and reducing industrial production efficiency; if the initiator is too much, the number of free radicals generated will be too much. Too many free radicals may cause an increase in side reactions, thereby affecting the performance of the prepared organic polymer carbon source.
[0015] Furthermore, the coupling agent is used to regulate the molecular weight of the prepared organic polymer carbon source. During the reaction, if too little coupling agent is added, the molecular weight of the prepared organic polymer carbon source will be too small, which will lead to the weakening of the interfacial bonding force between the organic polymer carbon source and the lithium iron phosphate during the process of coating lithium iron phosphate with the organic polymer carbon source with a smaller molecular weight, that is, the adsorption of the organic polymer carbon source on the surface of the lithium iron phosphate will be slightly weaker, and then it will be difficult to form a uniform coating layer on the surface of the lithium iron phosphate particles; and if the coupling agent is used in excessive amounts, it is easy to form an overly thick coating layer on the surface of the lithium iron phosphate particles, thereby hindering the transmission of lithium ions.
[0016] In this embodiment, if the content of ether monomers is too little, the molecular weight of the generated organic polymer carbon source will be relatively small, so that the viscosity of the organic polymer carbon source will be relatively low and the dispersibility will be better; however, in the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the hydrogen bonding effect of the ether molecules is weakened due to the low content of ether monomers, resulting in the weakening of the interaction between the organic polymer carbon source and the lithium iron phosphate, so that the adhesion of the coating layer is weakened, thereby showing that the coating is not dense enough or the thickness is insufficient; and if the content of ether monomers is too much, the molecular weight of the generated organic polymer carbon source will be relatively large, so that the viscosity of the organic polymer carbon source will be relatively high and the dispersibility will be poor; in the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, although the hydrogen bonding effect of the ether molecules is enhanced due to the excessive content of ether monomers, the interaction between the organic polymer carbon source and the lithium iron phosphate is enhanced, the poorly dispersible organic polymer carbon source will lead to an uneven coating layer.
[0017] Therefore, in the present application, by limiting the molar ratio of benzene ring monomers, phosphonic acid monomers and ether monomers to (0.05-0.50): (0.01-0.20): (0.1-0.3), and the molar ratio of initiator, benzene ring monomer and coupling agent to (0.10-0.20): (0.05-0.50): (0.01-0.03), an organic polymer carbon source with moderate molecular weight and excellent dispersion and coating properties can be prepared to achieve performance optimization.
[0018] In some embodiments, the alcohol containing unsaturated double bonds is at least one of 3-butene-1,2-diol and ethylene glycol; and / or, the ether monomer is at least one of distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether; and / or, the benzene ring monomer is at least one of distyrylphenol polyoxyethylene ether, styrene, hydroquinone and phenylene; and / or, the phosphonic acid monomer is at least one of allylphosphonic acid and vinylidene-1,1-diphosphonic acid; and / or, the reducing agent is at least one of vitamin C and citric acid; and / or, the chain transfer agent is at least one of mercaptopropionic acid and thioglycolic acid; and / or, the initiator is at least one of hydrogen peroxide and vitamin C; and / or, the coupling agent is at least one of anilinemethyltrimethoxysilane and azobenzene-3,3-dicarboxylic acid.
[0019] In this embodiment, the alcohol containing an unsaturated double bond is at least one of 3-butene-1,2-diol and ethylene glycol, wherein both 3-butene-1,2-diol and ethylene glycol contain an alcohol group and have good hydrophilicity. At the same time, 3-butene-1,2-diol and ethylene glycol also contain unsaturated double bonds. Using the unsaturated double bonds as reaction sites, reactions with various other groups can be achieved.
[0020] Further, the ether monomer is at least one of distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether, wherein distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether are selected as ether monomers, which are all macromolecular monomers, and can effectively improve the encapsulation performance of the prepared organic polymer carbon source; At the same time, the ether monomer with a long side chain has excellent hydrophilicity, which helps to improve the water solubility of the prepared organic polymer carbon source. In addition, the ether monomer used has a higher reactivity, which is conducive to controlling the polymerization process, thereby preparing an organic polymer carbon source.
[0021] Furthermore, by selecting at least one of distyrylphenol polyoxyethylene ether, styrene, hydroquinone and terephthalene as the benzene ring monomer, a high-quality carbon source can be provided.
[0022] Furthermore, by selecting at least one of allylphosphonic acid and vinylidene-1,1-diphosphonic acid as the phosphonic acid monomer, the selective adsorption effect of the organic polymer carbon source can be improved.
[0023] Furthermore, by selecting at least one of vitamin C and citric acid as the reducing agent, the raw materials are easy to obtain and the cost is low; in addition, the residual vitamin C and citric acid undergo a carbonization process when applied in the preparation process of lithium iron phosphate and can be converted into a coated carbon layer.
[0024] Furthermore, by selecting at least one of anilinemethyltrimethoxysilane and azobenzene-3,3-dicarboxylic acid as a coupling agent, the prepared organic polymer carbon source can have controllable particle size and excellent electrical properties through its connection characteristics.
[0025] In a second aspect, an embodiment of the present application provides an organic polymer carbon source, which is prepared by the above-mentioned method for preparing an organic polymer carbon source.
[0026] In the technical solution of the embodiment of the present application, by using the organic polymer carbon source as the carbon source to prepare lithium iron phosphate, the problems of uneven carbon coating, poor consistency of particle growth, and large fluctuations in compaction density and electrical properties existing in the existing lithium iron phosphate preparation process can be effectively solved.
[0027] In a third aspect, an embodiment of the present application provides a positive electrode material, and a preparation method of the positive electrode material includes: mixing iron phosphate, a lithium source, a magnesium source, an organic polymer carbon source and water, and obtaining a lithium iron phosphate positive electrode material through dispersion, drying and sintering, wherein the organic polymer carbon source is the above-mentioned organic polymer carbon source.
[0028] In the technical solution of the embodiment of the present application, in order to maintain the balance of the reaction and compensate for possible cation vacancies, additional metal ions need to be introduced, wherein by introducing magnesium ions, magnesium ions have the same valence state as ferrous iron and can effectively occupy vacant iron sites, which not only inhibits excessive crystal growth but also helps to improve the ionic conductivity of the material.
[0029] Among them, in the preparation process of lithium iron phosphate, firstly, iron phosphate, lithium source, magnesium source, organic polymer carbon source and water are mixed, and a precursor material is obtained by dispersion treatment. Thereafter, the precursor material is dried and sintered to obtain a lithium iron phosphate positive electrode material. Specifically, in the present application, the dispersion step can be performed by sand grinding to obtain a uniformly mixed precursor material. This step can not only enhance the sphericity of the precursor material, but also improve the efficiency of the subsequent sintering reaction of the precursor material, thereby facilitating the preparation of high-density lithium iron phosphate materials.
[0030] It is understandable that in the present application, after the step of preparing lithium iron phosphate by sintering, the lithium iron phosphate is further crushed and demagnetized to obtain a lithium iron phosphate material with a low impurity content.
[0031] In some embodiments, the molar ratio of iron phosphate, lithium source, magnesium source and organic polymer carbon source is 1: (0.50-0.54): (0.0034-0.0038): (0.0057-0.0060).
[0032] In this embodiment, by setting the molar ratio of iron phosphate, lithium source, magnesium source and organic polymer carbon source to 1: (0.50~0.54): (0.0034~0.0038): (0.0057~0.0060), the prepared lithium iron phosphate has better performance and is not prone to excessive waste of raw materials, which is beneficial to controlling production costs.
[0033] In some embodiments, the carbon content of the positive electrode material is 1.22-1.24%, the average primary particle size is 0.22-0.25 μm, and the compaction density is 2.52-2.56 g / cm 3 .
[0034] In this embodiment, the carbon content is controlled between 1.22% and 1.24%. The carbon coating within this range helps to improve the conductivity of the material and ensure the efficient transmission of electrons during the charge and discharge process without increasing the weight too much, which is beneficial to improving the energy density and cycle stability of the battery. The average primary particle size is between 0.22 and 0.25 μm. Such micronization can increase the specific surface area of the material, which is beneficial to the penetration of the electrolyte and the full contact of the active substance, thereby increasing the electrochemical reaction rate, reducing the internal resistance, and enhancing the high current discharge capacity of the battery. The compaction density is between 2.52 and 2.56 g / cm 3 range, indicating that the material can withstand a higher degree of compaction when assembled into a battery, which helps to increase the energy density of the battery.
[0035] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, comprising the above-mentioned positive electrode material.
[0036] In this embodiment, the positive electrode plate contains the above-mentioned positive electrode material, and thus has the advantages of more uniform carbon coating, more stable particle size and compaction density.
[0037] In a fifth aspect, an embodiment of the present application provides a secondary battery, comprising the above-mentioned positive electrode plate.
[0038] In this embodiment, the secondary battery includes the above-mentioned positive electrode plate, and thus has the advantage of more stable electrical performance.
[0039] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0041] Figure 1 This is the infrared spectrum of the organic polymer carbon source prepared in Example 4.
[0042] Figure 2 This is the SEM image of the lithium iron phosphate product in Comparative Example 1.
[0043] Figure 3 This is the primary particle size distribution diagram of the lithium iron phosphate product in Comparative Example 1.
[0044] Figure 4 This is the SEM image of the carbon-coated lithium iron phosphate material prepared in Example 5.
[0045] Figure 5 This is the primary particle size distribution diagram of the carbon-coated lithium iron phosphate material prepared in Example 5. DETAILED DESCRIPTION
[0046] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0048] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0049] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0050] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0051] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0052] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0053] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0054] The existing lithium iron phosphate preparation has technical problems such as uneven carbon coating, inconsistent particle growth, and large fluctuations in compaction density and electrical properties.
[0055] In order to solve the technical problems of uneven carbon coating, inconsistent particle growth, and large fluctuations in compaction density and electrical properties, the present application provides an organic polymer carbon source and a preparation method thereof, a positive electrode material and a secondary battery. By preparing an organic polymer carbon source, the technical effects of uniform carbon coating, good consistency in particle growth, and small fluctuations in compaction density and electrical properties can be achieved, thereby improving the electrical stability of the positive electrode sheet and the secondary battery.
[0056] In a first aspect, the present invention provides a method for preparing an organic polymer carbon source, comprising the following steps: Mixing alcohol and ether monomers containing unsaturated double bonds with water to obtain a base material; Mixing a benzene ring monomer, a reducing agent and water to obtain a first mixture; mixing a phosphonic acid monomer, a chain transfer agent and water to obtain a second mixture; An initiator, a first mixture, a second mixture and a coupling agent are added to the base material to obtain an organic polymer carbon source through reaction.
[0057] In the present application, alcohols and ether monomers containing unsaturated double bonds are mixed to form a base material; thereafter, a first mixture and a second mixture are prepared respectively; after adding an initiator, a first mixture, a second mixture and a coupling agent to the base material, since the concentration of ether monomers in the base material is the highest, the alcohols and ether monomers containing unsaturated double bonds in the base material will first undergo polymerization to obtain polymerization products; benzene ring monomers and phosphonic acid monomers will undergo end-capping reactions at the end groups in the presence of coupling agents and initiators; the end-capping reaction products and the polymerization products together constitute an organic polymer carbon source. Figure 1 The infrared spectrum of the organic polymer carbon source shows that the double bond participates in the reaction process, while the alcohol hydroxyl group, ether group, phosphonic acid group and benzene ring structure do not participate in the reaction and are thus retained.
[0058] Understandably, in the present application, the organic polymer carbon source has alcoholic hydroxyl groups, and the excellent hydrophilicity of the alcoholic hydroxyl groups makes the prepared organic polymer carbon source have good water solubility; at the same time, the alcoholic hydroxyl groups have adsorption and complexing capabilities. When the organic polymer carbon source is applied to the preparation of lithium iron phosphate, the alcoholic hydroxyl groups carried by the organic polymer carbon source can not only effectively disperse the agglomerated particles produced in the sand milling and spraying processes, but also can precisely control the particle size, morphology and distribution range of the prepared lithium iron phosphate. In addition, during the sintering stage in the preparation process of lithium iron phosphate, the alcoholic hydroxyl groups carried by the organic polymer carbon source can also guide the growth behavior of lithium iron phosphate, thereby optimizing the structure and performance of the prepared lithium iron phosphate.
[0059] Furthermore, the organic polymer carbon source also has a benzene ring structure, an ether group and a phosphonic acid group, wherein the benzene ring structure is helpful for dispersion, and the ether group has good water solubility and dispersibility. Therefore, when the organic polymer carbon source is applied to the preparation of lithium iron phosphate, during the process of drying and sintering to achieve carbon coating, better coating and dispersion of the carbon layer can be achieved. In particular, in the present application, the benzene ring structure is easy to directly carbonize at high temperature, and can provide an efficient conductive carbon network. The phosphonic acid group has strong adsorption properties, and combined with the efficient bridging effect of the coupling agent, the carbon coating structure can be further optimized.
[0060] In some embodiments, the molar ratio of alcohols and ether monomers containing unsaturated double bonds to water is (2.5-3.5): (0.1-0.3): (10-20); and / or, in the step of preparing the first mixture, the molar ratio of the benzene ring monomer, the reducing agent and water is (0.05-0.40): (0.001-0.005): (5-10); and / or, in the step of preparing the second mixture, the molar ratio of the phosphonic acid monomer, the chain transfer agent and water is (0.01-0.20): (0.01-0.02): (5-10).
[0061] In this embodiment, by setting the molar ratio of the unsaturated double bond alcohol and ether monomers to water contained in the base material to (2.5-3.5): (0.1-0.3): (10-20), the molar ratio of the benzene ring monomer, the reducing agent and the water contained in the first mixture is set to (0.05-0.40): (0.001-0.005): (5-10), and at the same time, the molar ratio of the phosphonic acid monomer, the chain transfer agent and the water contained in the second mixture is set to (0.01-0.20): (0.01-0.02): (5-10), the prepared organic polymer carbon source has better performance, is less likely to cause excessive waste of raw materials, and is conducive to controlling production costs.
[0062] Specifically, in this embodiment, the molar ratio of the alcohol or ether monomer containing an unsaturated double bond to water can be 2.5:0.1:10, 2.5:0.2:10, 2.5:0.3:10, 3.0:0.1:10, 3.0:0.2:10, 3.0:0.3:10, 3.5:0.1:10, 3.5:0.2:10, 3.5:0.3:10, 2.5:0.1:20, 2.5:0. 2:20, 2.5:0.3:20, 2.5:0.1:15, 2.5:0.2:15, 2.5:0.3:15, 3.0:0.1:15, 3.0:0.2:15, 3.0:0.3:15, 3.5:0.1:15, 3.5:0.2:15, 3.5:0.3:15 or any ratio within the range of (2.5~3.5):(0.1~0.3):(10~20).
[0063] Specifically, in this embodiment, the molar ratio of the benzene ring monomer, the reducing agent and water is 0.05:0.001:5, 0.05:0.003:5, 0.05:0.005:5, 0.1:0.001:5, 0.1:0.003:5, 0.1:0.005:5, 0.2:0.001:5, 0.2:0.003:5, 0.2:0.005:5, 0.4:0.001:5, 0.4:0.003:5, 0.4:0.005:5, 0.1:0.001:8, 0.1:0.003:8, 0.1:0.005:8, 0.2:0.001:5 8, 0.2: 0.003:8, 0.2: 0.005:8, 0.4: 0.001:8, 0.4: 0.003:8, 0.4: 0.005:8, 0.1: 0.001:10, 0.1: 0.003:10, 0.1: 0.005:10, 0.2: 0.001:10, 0.2: 0.003:10, 0.2: 0.005:10, 0.4: 0.001:10, 0.4: 0.003:10, 0.4: 0.005:10 or any ratio within the range of (0.05~0.40): (0.001~0.005): (5~10).
[0064] Specifically, in this embodiment, the molar ratio of the phosphonic acid monomer, the chain transfer agent and water can be 0.01:0.01:5, 0.01:0.15:5, 0.01:0.02:5, 0.1:0.01:5, 0.1:0.15:5, 0.1:0.02:5, 0.2:0.01:5, 0.2:0.15:5, 0.2:0.02:5, 0.01:0.01:8, 0.01:0.15:8, 0.01:0.02:8, 0.1:0.01:8, 0.1:0.15:8, 0.1:0.02:8. 1: 0.02:8, 0.2: 0.01:8, 0.2: 0.15:8, 0.2: 0.02:8, 0.01: 0.01:10, 0.01: 0.15:10, 0.01: 0.02:10, 0.1: 0.01:10, 0.1: 0.15:10, 0.1: 0.02:10, 0.2: 0.01:10, 0.2: 0.15:10, 0.2: 0.02:10 or any ratio within the range of (0.01~0.20): (0.01~0.02): (5~10).
[0065] In the present application, the molar ratio of the benzene ring monomer in the first mixture, the phosphonic acid monomer in the second mixture and the ether monomer in the base material is (0.05~0.50):(0.01~0.20):(0.1~0.3); and / or, the molar ratio of the initiator, the benzene ring monomer in the first mixture and the coupling agent is (0.10~0.20):(0.05~0.50):(0.01~0.03).
[0066] In this embodiment, the phosphonic acid monomer contains a phosphonic acid group, and the phosphonic acid group gives the prepared organic polymer carbon source a strong adsorption property. If the content of the phosphonic acid monomer in the second mixture is too low, the phosphonic acid group contained in the generated organic polymer carbon source is too small, and in the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the adsorption between the phosphonic acid group and the lithium iron phosphate is weak, resulting in low adhesion of the organic polymer carbon source, making the coating layer adhesion effect poor; and if the content of the phosphonic acid monomer in the second mixture is too high, the phosphonic acid group contained in the generated organic polymer carbon source is too much, and in the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the adsorption between the phosphonic acid group and the lithium iron phosphate is strong, resulting in local aggregation of the organic polymer carbon source, making the coating layer thickness uneven.
[0067] Furthermore, the benzene ring monomer contains a benzene ring structure, and the benzene ring structure gives the prepared organic polymer carbon source good dispersibility. If the benzene ring monomer content in the first mixture is too low, the benzene ring structure contained in the generated organic polymer carbon source is too small. In the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the dispersibility of the organic polymer carbon source in the solution will decrease, and agglomeration is likely to occur, resulting in uneven thickness of the carbon coating layer; and if the benzene ring monomer content in the first mixture is too high, the benzene ring structure contained in the generated organic polymer carbon source is too much, resulting in increased hydrophobicity of the organic polymer carbon source. In the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the organic polymer carbon source is difficult to fully disperse in the solution, making the subsequent carbon coating process difficult.
[0068] Furthermore, the initiator is used to regulate the polymerization reaction rate and indirectly affect the molecular weight of the organic polymer carbon source. If the initiator is too little, the number of free radicals generated will be too little, thereby slowing down the polymerization reaction rate, prolonging the polymerization reaction time, and reducing industrial production efficiency; if the initiator is too much, the number of free radicals generated will be too much. Too many free radicals may cause an increase in side reactions, thereby affecting the performance of the prepared organic polymer carbon source.
[0069] Furthermore, the coupling agent is used to regulate the molecular weight of the prepared organic polymer carbon source. During the reaction, if too little coupling agent is added, the molecular weight of the prepared organic polymer carbon source will be too small, which will lead to the weakening of the interfacial bonding force between the organic polymer carbon source and the lithium iron phosphate during the carbon coating of lithium iron phosphate using the organic polymer carbon source with a smaller molecular weight, that is, the adsorption of the organic polymer carbon source on the surface of the lithium iron phosphate will be slightly weaker, and then it will be difficult to form a uniform coating layer on the surface of the lithium iron phosphate particles; and if the coupling agent is used in excessive amounts, it is easy to form an overly thick coating layer on the surface of the lithium iron phosphate particles, thereby hindering the transmission of lithium ions.
[0070] Furthermore, if the content of ether monomers is too little, the molecular weight of the generated organic polymer carbon source will be relatively small, so that the viscosity of the organic polymer carbon source will be relatively low and the dispersibility will be better; however, in the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, the hydrogen bonding effect of the ether molecules is weakened due to the low content of ether monomers, resulting in the weakening of the interaction between the organic polymer carbon source and the lithium iron phosphate, so that the adhesion of the coating layer is weakened, thereby showing that the coating is not dense enough or the thickness is insufficient; and if the content of ether monomers is too much, the molecular weight of the generated organic polymer carbon source will be relatively large, so that the viscosity of the organic polymer carbon source will be relatively high and the dispersibility will be poor; in the process of carbon-coating lithium iron phosphate with the organic polymer carbon source, although the hydrogen bonding effect of the ether molecules is enhanced due to the excessive content of ether monomers, so that the interaction between the organic polymer carbon source and the lithium iron phosphate is enhanced, the poorly dispersible organic polymer carbon source will lead to an uneven coating layer.
[0071] Therefore, in the present application, by limiting the molar ratio of benzene ring monomers, phosphonic acid monomers and ether monomers to (0.05-0.50): (0.01-0.20): (0.1-0.3), and the molar ratio of initiator, benzene ring monomer and coupling agent to (0.10-0.20): (0.05-0.50): (0.01-0.03), an organic polymer carbon source with moderate molecular weight and excellent dispersion and coating properties can be prepared to achieve performance optimization.
[0072] Specifically, in this embodiment, the molar ratios of the benzene ring monomer, the phosphonic acid monomer, and the ether monomer are 0.05:0.01:0.1, 0.05:0.1:0.1, 0.05:0.2:0.1, 0.1:0.01:0.1, 0.1:0.1:0.1, 0.1:0.2:0.1, 0.2:0.01:0.1, 0.2:0.1:0 .1, 0.2: 0.2: 0.1, 0.5: 0.01: 0.1, 0.5: 0.1: 0.1, 0.5: 0.2: 0.1, 0.05: 0.01: 0.2, 0.05: 0.1: 0.2, 0.05: 0.2: 0.2, 0.1: 0.01: 0.2, 0.1: 0.1: 0.2, 0.1: 0.2: 0.2, 0.2 : 0.01: 0.2, 0.2: 0.1: 0.2, 0.2: 0.2: 0.2, 0.5: 0.01: 0.2, 0.5: 0.1: 0.2, 0.5: 0.2: 0.2, 0.05: 0.01: 0.3, 0.05: 0.1: 0.3, 0.05: 0.2: 0.3, 0.1: 0.01: 0.3, 0.1: 0.1: 0.3, 0.1:0.2:0.3, 0.2:0.01:0.3, 0.2:0.1:0.3, 0.2:0.2:0.3, 0.5:0.01:0.3, 0.5:0.1:0.3, 0.5:0.2:0.3 or any ratio within the range of (0.05~0.50):(0.01~0.20):(0.1~0.3).
[0073] Specifically, in this embodiment, the molar ratio of the initiator, the benzene ring monomer and the coupling agent can be 0.10:0.05:0.01, 0.10:0.1:0.01, 0.10:0.3:0.01, 0.10:0.5:0.01, 0.20:0.05:0.01, 0.20:0.1:0.01, 0.20:0.3:0.01, 0.20:0.5:0.01, 0.10:0.05:0.02, 0.10:0.1:0.02, 0.10:0.3:0.02, 0.10:0.5:0.02, 0.20:0 .05:0.02, 0.20:0.1:0.02, 0.20:0.3:0.02, 0.20:0.5:0.02, 0.10:0.05:0.03, 0.10:0.1:0.03, 0.10:0.3:0.03, 0.10:0.5:0.03, 0.20:0.05:0.03, 0.20:0.1:0.03, 0.20:0.3:0.03, 0.20:0.5:0.03 or any ratio within the range of (0.10~0.20):(0.05~0.50):(0.01~0.03).
[0074] In the present application, the alcohol containing unsaturated double bonds is at least one of 3-butene-1,2-diol and ethylene glycol; and / or, the ether monomer is at least one of distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether; and / or, the benzene ring monomer is at least one of distyrylphenol polyoxyethylene ether, styrene, hydroquinone and phenylene; and / or, the phosphonic acid monomer is at least one of allylphosphonic acid and vinylidene-1,1-diphosphonic acid; and / or, the reducing agent is at least one of vitamin C and citric acid; and / or, the chain transfer agent is at least one of mercaptopropionic acid and thioglycolic acid; and / or, the initiator is at least one of hydrogen peroxide and vitamin C; and / or, the coupling agent is at least one of anilinemethyltrimethoxysilane and azobenzene-3,3-dicarboxylic acid.
[0075] In this embodiment, the alcohol containing an unsaturated double bond is at least one of 3-butene-1,2-diol and ethylene glycol, wherein both 3-butene-1,2-diol and ethylene glycol contain an alcohol group and have good hydrophilicity. At the same time, 3-butene-1,2-diol and ethylene glycol also contain unsaturated double bonds. Using the unsaturated double bonds as reaction sites, reactions with various other groups can be achieved.
[0076] Further, the ether monomer is at least one of distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether, wherein distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether are selected as ether monomers, which are all macromolecular monomers, and can effectively improve the encapsulation performance of the prepared organic polymer carbon source; At the same time, the ether monomer with a long side chain has excellent hydrophilicity, which helps to improve the water solubility of the prepared organic polymer carbon source. In addition, the ether monomer used has a higher reactivity, which is conducive to controlling the polymerization process, thereby preparing an organic polymer carbon source.
[0077] In some embodiments, the ether monomer can also be a mixture of 4-hydroxybutyl vinyl ether and isopentanol polyoxyethylene ether in a mass ratio of 2:1, or a mixture of ethylene glycol monovinyl polyoxyethylene ether and 4-hydroxybutyl vinyl ether in a mass ratio of 3:1, as well as a mixture of other multiple monomers mixed in a certain proportion.
[0078] Furthermore, by selecting at least one of distyrylphenol polyoxyethylene ether, styrene, hydroquinone and terephthalene as the benzene ring monomer, a high-quality carbon source can be provided.
[0079] In some embodiments, the benzene ring monomer can also be a mixture of distyrylphenol polyoxyethylene ether and styrene in a mass ratio of 2:1, a mixture of distyrylphenol polyoxyethylene ether and hydroquinone in a mass ratio of 2:1, a mixture of distyrylphenol polyoxyethylene ether and hydroquinone in a mass ratio of 1:1, a mixture of distyrylphenol polyoxyethylene ether, hydroquinone and styrene in a mass ratio of 2:1:1, and a mixture of multiple other monomers mixed in a certain proportion.
[0080] Furthermore, by selecting at least one of allylphosphonic acid and vinylidene-1,1-diphosphonic acid as the phosphonic acid monomer, the selective adsorption effect of the organic polymer carbon source can be improved.
[0081] Furthermore, by selecting at least one of vitamin C and citric acid as the reducing agent, the raw materials are easy to obtain and the cost is low; in addition, the residual vitamin C and citric acid undergo a carbonization process when used in the preparation process of lithium iron phosphate and can be converted into a coated carbon layer, and no additional impurities are introduced in this process.
[0082] Furthermore, by selecting at least one of aniline methyl trimethoxysilane and azobenzene-3,3-dicarboxylic acid as a coupling agent, the prepared organic polymer carbon source can have controllable particle size and excellent electrical properties through its connection characteristics. For example, the coupling agent can be azobenzene-3,3-dicarboxylic acid, aniline methyl trimethoxysilane, azobenzene-3,3-dicarboxylic acid, or a mixture of aniline methyl trimethoxysilane in a mass ratio of 1:1.
[0083] Furthermore, the initiator is selected from hydrogen peroxide, and may also be a mixture of hydrogen peroxide and vitamin C. Preferably, the initiator is a mixture of vitamin C and hydrogen peroxide in a mass ratio of 1:7.
[0084] In a second aspect, an embodiment of the present application provides an organic polymer carbon source, which is prepared by the above-mentioned method for preparing an organic polymer carbon source.
[0085] Among them, by using the organic polymer carbon source as the carbon source to prepare lithium iron phosphate, the problems of uneven carbon coating, poor consistency of particle growth, and large fluctuations in compaction density and electrical properties are effectively solved.
[0086] In a third aspect, an embodiment of the present application provides a positive electrode material, and a preparation method of the positive electrode material includes: mixing iron phosphate, a lithium source, a magnesium source, an organic polymer carbon source and water, and obtaining a lithium iron phosphate positive electrode material through dispersion, drying and sintering, wherein the organic polymer carbon source is the above-mentioned organic polymer carbon source.
[0087] In order to maintain the balance of the reaction and compensate for possible cation vacancies, additional metal ions need to be introduced. Among them, magnesium ions, because they have the same valence state as ferrous iron, can effectively occupy vacant iron sites, which not only inhibits excessive crystal growth but also helps to improve the ionic conductivity of the material.
[0088] Among them, in the preparation process of lithium iron phosphate, iron phosphate, lithium source, magnesium source, organic polymer carbon source and water are first mixed, and a precursor material is obtained by dispersion treatment. Thereafter, the precursor material is dried and sintered to obtain a lithium iron phosphate positive electrode material. Specifically, in the present application, the dispersion step can be performed by sand milling to obtain a uniformly mixed precursor material. This step can not only enhance the sphericity of the precursor material, but also improve the efficiency of the subsequent sintering reaction of the precursor material, thereby facilitating the preparation of high-density lithium iron phosphate materials.
[0089] It is understandable that in the present application, after the step of preparing lithium iron phosphate by sintering, the lithium iron phosphate is further crushed and demagnetized to obtain a lithium iron phosphate material with a low impurity content.
[0090] Furthermore, in some embodiments, the ferric phosphate is anhydrous ferric phosphate because of its high ratio of phosphorus to iron, which helps to significantly reduce the generation of elemental iron and iron phosphide by-products.
[0091] In the technical solution of the embodiment of the present application, the molar ratio of iron phosphate, lithium source, magnesium source and organic polymer carbon source is 1: (0.50~0.54): (0.0034~0.0038): (0.0057~0.0060).
[0092] In this embodiment, by setting the molar ratio of iron phosphate, lithium source, magnesium source and organic polymer carbon source to 1: (0.50~0.54): (0.0034~0.0038): (0.0057~0.0060), the prepared lithium iron phosphate has better performance and is not prone to excessive waste of raw materials, which is beneficial to controlling production costs.
[0093] In some embodiments, the sintering process includes: sintering for 8 to 10 hours under a protective atmosphere of 780 to 800°C, and the protective atmosphere is nitrogen with a purity of 99.999%. Preferably, the sintering temperature is 780°C and the sintering time is 10 hours. Understandably, when sintering under a protective atmosphere, if the sintering temperature is too low, the lithium iron phosphate reaction will be insufficient, thereby affecting the compaction density; and if the sintering temperature exceeds 800°C, undesirable magnetic byproducts such as iron phosphide are easily produced. Therefore, it is necessary to precisely control the sintering temperature and appropriately adjust the holding time to ensure that the reaction is fully carried out while avoiding unnecessary side reactions.
[0094] In some embodiments, the lithium iron phosphate material obtained after sintering is pulverized until the D50 of the lithium iron phosphate material is any value between 0.85 and 1.05 μm. Preferably, the lithium iron phosphate material is pulverized to a D50 of 0.90 μm. Understandably, if the pulverized particle size is too small, the bulk density will be too small, which is not conducive to the uniform distribution and speed control of the material during the packaging process; and if the pulverized particle size is too large, large particles are easily wrapped by smaller particles during homogenization, reducing the effective contact area with the electrolyte, thereby affecting the electrical performance of the secondary battery prepared using lithium iron phosphate.
[0095] In some embodiments, spray drying is selected for drying. Spray drying technology exhibits superior granulation performance and can effectively promote the sand-milled precursor to form uniform spherical particles through an atomizer. Among them, the inlet air temperature is an important parameter affecting the drying efficiency and product yield; the outlet air temperature is directly related to the residual moisture content of the spray material, and high moisture content will increase the humidity in the furnace during sintering, thereby negatively affecting the uniformity and efficiency of carbon coating. In addition, the amplitude stability of the atomizer is crucial to maintaining the consistency of the spray particle size; the more stable the amplitude, the more uniform the particle size distribution obtained by the spray, which is extremely critical for improving the physical uniformity and electrochemical performance consistency of the sintered product. In this application, a centrifugal spray drying unit is preferably used, model LPG-45, the inlet air temperature is set to 240°C, the outlet air temperature is controlled at 90°C, the pressure of the spray feed pump is 0.062MPa, the operating speed of the atomizer is 35Hz, and the droplet particle size distribution is in the range of 8~12um.
[0096] In the technical solution of the embodiment of the present application, the carbon content of the positive electrode material is 1.22~1.24%, the average primary particle size is 0.22~0.25μm, and the compaction density is 2.52~2.56g / cm 3 .
[0097] Among them, the carbon content is controlled between 1.22% and 1.24%. The carbon coating within this range helps to improve the conductivity of the material and ensure the efficient transmission of electrons during the charging and discharging process without increasing the weight too much, which is beneficial to improving the energy density and cycle stability of the battery. Furthermore, after sintering, the average primary particle size is pulverized to be between 0.22 and 0.25 μm. The micronization process can increase the specific surface area of the material, which is beneficial to the penetration of the electrolyte and the full contact of the active substance, thereby increasing the electrochemical reaction rate, reducing the internal resistance, and enhancing the battery's large current discharge capacity. Understandably, the compaction density is between 2.52 and 2.56 g / cm 3 range, indicating that the material can withstand a higher degree of compaction when assembled into a battery, which helps to increase the energy density of the battery.
[0098] In a fourth aspect, an embodiment of the present application provides a positive electrode plate, comprising the above-mentioned positive electrode material.
[0099] In a fifth aspect, an embodiment of the present application provides a secondary battery, comprising the above-mentioned positive electrode plate.
[0100] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0101] 1. Preparation method Example 1 A method for preparing an organic polymer carbon source comprises the following steps: (1) In a 2-ton reactor, first add 271.5 kg of 3-butene-1,2-diol, 160.6 kg of ethylene glycol monovinyl polyoxyethylene ether with a molecular weight of 800, and 280 kg of pure water as reaction base materials, and heat with steam and stir to 40°C; (2) mixing 28.5 kg of distyrylphenol polyoxyethylene ether and styrene in a mass ratio of 2:1, adding 0.65 kg of vitamin C and 120 kg of pure water, and stirring evenly to obtain a first mixture; (3) Mix 18.9 kg of allylphosphonic acid and 1.4 kg of thioglycolic acid, add 90 kg of pure water, and stir evenly to obtain a second mixture; (4) When the temperature of the reactor is stable at 40°C, add 4.0 kg of hydrogen peroxide and stir for 5 minutes. Then, start to drip the first mixture and the second mixture at a uniform speed at the same time. The dripping time of the first mixture is 60 minutes, and the dripping time of the second mixture is 50 minutes. When the dripping of the first mixture is 40 minutes, add 5.3 kg of aniline methyl trimethoxy silane at one time; after the dripping of the first mixture is completed, continue to stir and heat to 60°C, keep the reaction at this temperature for 60 minutes, and finally cool the system naturally to room temperature.
[0102] Through the above steps, an organic polymer carbon source with a molecular weight of 3500-4000 and a mass fraction of 50% was successfully obtained.
[0103] Example 2 A method for preparing an organic polymer carbon source comprises the following steps: (1) In a 2-ton reactor, first add 274.5 kg of 3-butene-1,2-diol, 165.6 kg of 4-hydroxybutyl vinyl ether with a molecular weight of 800, and 280 kg of pure water as reaction base materials, and heat with steam and stir to 40°C; (2) mixing 30.5 kg of distyrylphenol polyoxyethylene ether and hydroquinone in a mass ratio of 2:1, adding 0.60 kg of vitamin C and 120 kg of pure water, and stirring evenly to obtain a first mixture; (3) Mix 18.9 kg of vinylidene-1,1-diphosphonic acid (CAS No. 34162-79-3, purchased from Shaoxing Xiechuang Chemical Technology Co., Ltd.) and 1.4 kg of mercaptopropionic acid, then add 80 kg of pure water, and stir evenly to obtain a second mixture; (4) When the temperature of the reactor stabilizes at 40°C, add 3.8 kg of hydrogen peroxide and stir for 5 minutes. Then, start to drip the first mixture and the second mixture at a uniform speed at the same time. The dripping time of the first mixture is 60 minutes, and the dripping time of the second mixture is 50 minutes. When the dripping of the first mixture is 40 minutes, add 5.3 kg of azobenzene-3,3-dicarboxylic acid at one time; after the dripping of the first mixture is completed, continue to stir and heat to 60°C, keep the reaction at this temperature for 60 minutes, and finally cool the system naturally to room temperature.
[0104] Through the above steps, an organic polymer carbon source with a molecular weight of about 4000 and a mass fraction of 50% was successfully obtained.
[0105] Example 3 A method for preparing an organic polymer carbon source comprises the following steps: (1) In a 2-ton reactor, firstly, 274.5 kg of 3-butene-1,2-diol, 165.6 kg of a mixture of 4-hydroxybutyl vinyl ether and isopentanol polyoxyethylene ether, each with a molecular weight of 800, and 280 kg of pure water were added as reaction base materials, and the mixture was heated to 40° C. by steam heating and stirring; wherein the mass ratio of 4-hydroxybutyl vinyl ether to isopentanol polyoxyethylene ether was 2:1; (2) Mix 32.3 kg of distyrylphenol polyoxyethylene ether and p-phenylene glycol in a mass ratio of 1:1, add 0.55 kg of vitamin C and 120 kg of pure water, and stir evenly to obtain a first mixture; (3) Mix 17.9 kg of allylphosphonic acid and 1.3 kg of mercaptopropionic acid, add 80 kg of pure water, and stir evenly to obtain a second mixture; (4) When the temperature of the reactor is stable at 40°C, add 3.6 kg of hydrogen peroxide and stir for 5 minutes. Then, start to drip the first mixture and the second mixture at a uniform speed at the same time. The dripping time of the first mixture is 60 minutes, and the dripping time of the second mixture is 50 minutes. When the first mixture is dripped for 40 minutes, add 5.6 kg of a mixture of azobenzene-3,3-dicarboxylic acid and aniline methyl trimethoxysilane with a mass ratio of 1:1 at one time; after the first mixture is dripped, continue to stir and heat to 60°C, keep the reaction at this temperature for 60 minutes, and finally cool the system naturally to room temperature.
[0106] Through the above steps, an organic polymer carbon source with a molecular weight of about 4000 and a mass fraction of 50% was successfully obtained.
[0107] Example 4 A method for preparing an organic polymer carbon source comprises the following steps: (1) In a 2-ton reactor, firstly, 277.5 kg of 3-butene-1,2-diol, 170.3 kg of a mixture of ethylene glycol monovinyl polyoxyethylene ether and 4-hydroxybutyl vinyl ether, each with a molecular weight of 800, and 280 kg of pure water were added as reaction base materials, and the mixture was heated to 40° C. by steam heating and stirring; wherein the mass ratio of ethylene glycol monovinyl polyoxyethylene ether to 4-hydroxybutyl vinyl ether was 3:1; (2) mixing 32.3 kg of distyrylphenol polyoxyethylene ether, hydroquinone and styrene in a mass ratio of 2:1:1, adding 0.55 kg of vitamin C and 120 kg of pure water, stirring evenly, to obtain a first mixture; (3) Mix 17.2 kg of allylphosphonic acid and 1.3 kg of mercaptopropionic acid, add 80 kg of pure water, and stir evenly to obtain a second mixture; (4) When the temperature of the reactor is stable at 40°C, add 3.85 kg of hydrogen peroxide and stir for 5 minutes. Then, start to drip the first mixture and the second mixture at a uniform speed at the same time. The dripping time of the first mixture is 60 minutes, and the dripping time of the second mixture is 50 minutes. When the dripping of the first mixture is 40 minutes, add 5.9 kg of azobenzene-3,3-dicarboxylic acid at one time; after the dripping of the first mixture is completed, continue to stir and heat to 60°C, keep the reaction at this temperature for 60 minutes, and finally cool the system naturally to room temperature.
[0108] Through the above steps, an organic polymer carbon source with a molecular weight of about 4000 and a mass fraction of 50% was successfully obtained.
[0109] Example 5 A method for preparing a positive electrode material, comprising the following steps: (1) The organic polymer carbon source prepared in Example 4, iron phosphate, lithium hydroxide and lithium carbonate, magnesium oxide and water were mixed to prepare a uniform slurry with a solid content of 49.1%; The addition ratio of each material is selected according to the molar ratio of iron to phosphorus in lithium iron phosphate being 1:1.04. Specifically, the mass of the organic polymer carbon source accounts for 9.1% of the mass of the iron phosphate, the mass ratio of lithium hydroxide to lithium carbonate is 2:1, and the total mass of lithium hydroxide and lithium carbonate accounts for 25.3% of the mass of the lithium iron phosphate; the addition amount of magnesium oxide accounts for 0.27% of the mass of the lithium iron phosphate; (2) The D50 of the particles in the slurry was adjusted to 0.25 μm by sand milling, and then spray dried at 245°C to obtain a precursor after controlled drying. The carbon content of the precursor accounted for 4.22% of the total mass, and the D50 of the obtained precursor powder was 20.4 μm. (3) The precursor obtained by spray drying is placed in a nitrogen protective atmosphere, heated to 780°C at a heating rate of 2°C / min, and kept at this temperature for 10 hours; then, the temperature is reduced to below 100°C by natural air cooling, and then the sample is taken out of the furnace and crushed to a D50 of 0.90 μm to obtain a lithium iron phosphate positive electrode material (specifically, a carbon-coated lithium iron phosphate material).
[0110] The carbon content of the final positive electrode material is 1.22% of the total mass.
[0111] Example 6 This embodiment provides a method for preparing a positive electrode material, which is different from Embodiment 5 only in that the organic polymer carbon source prepared in Embodiment 1 is used.
[0112] The carbon content of the final positive electrode material is 1.24% of the total mass.
[0113] Example 7 This embodiment provides a method for preparing a positive electrode material, which is different from Embodiment 5 only in that the organic polymer carbon source prepared in Embodiment 2 is used.
[0114] The carbon content of the final positive electrode material is 1.22% of the total mass.
[0115] Example 8 This embodiment provides a method for preparing a positive electrode material, which is different from Embodiment 5 only in that the organic polymer carbon source prepared in Embodiment 3 is used.
[0116] The carbon content of the final positive electrode material is 1.23% of the total mass.
[0117] Comparative Example 1 This embodiment provides a method for preparing a positive electrode material, which is different from Embodiment 5 only in that the carbon source uses glucose monohydrate in the same mass fraction as that in Embodiment 5, and the other process conditions remain the same.
[0118] 2. Test Method Carbon content test: using infrared carbon sulfur analyzer, model HCS-140.
[0119] Compacted density test: The test method refers to the compacted density measurement of lithium iron phosphate GB / T 7314-2005 standard, and an electronic compression testing machine is used for testing.
[0120] SEM test: The JSM6390 scanning electron microscope was used for testing, and the primary particle size and distribution were analyzed by Nano Measurer software.
[0121] Capacity test: 1. Preparation of CR2032 button cell: The positive electrode materials prepared in Examples 5 to 8 and the lithium iron phosphate product described in Comparative Example 1 were selected as positive electrode active materials, acetylene black was used as a conductive additive, and polytetrafluoroethylene (PTFE) was used as a binder. The positive electrode material, acetylene black, and polytetrafluoroethylene were mixed evenly in a mass ratio of 90:5:5 to prepare an electrode slurry. Subsequently, the slurry was coated on the current collector, dried and compacted to form an electrode sheet; the positive electrode sheet and the metal lithium sheet prepared above were used as negative electrodes, and assembled into CR2032 button cells respectively.
[0122] 2. Blue light test: The assembled battery was placed in an environment with a temperature controlled at 25±0.5℃ and a charge-discharge cycle test was performed in the voltage window range of 2V to 3.75V using a constant potential charge-discharge tester.
[0123] III. Analysis of test results of various embodiments and comparative examples The capacity test results of the batteries prepared in the embodiments and comparative examples are shown in Table 1.
[0124] Table 1 Capacity test statistics of batteries prepared in various embodiments and comparative examples
[0125] According to Table 1, it can be seen that the optimal solution for preparing lithium iron phosphate using an organic polymer carbon source is Example 5. The carbon-coated lithium iron phosphate prepared in Example 5 has the characteristics of low carbon content and high compaction density. Under 0.1C charge and discharge conditions, the electrochemical properties of the sample prepared in Example 5 and the sample prepared in Comparative Example 1 are similar. However, in the 1C discharge capacity test, the data measured by the sample prepared in Example 5 is significantly higher than the data measured by the sample prepared in Comparative Example 1, indicating that the carbon-coated lithium iron phosphate prepared using the organic polymer carbon source of the present invention has obvious advantages in 1C high-rate discharge performance.
[0126] In addition, multiple batches of samples produced continuously in Example 5 were selected to prepare CR2032 button batteries and conduct capacity tests, and the test data were summarized. For comparison, multiple batches of samples produced continuously in Comparative Example 1 were selected to prepare CR2032 button batteries and conduct capacity tests, and the test data were summarized, in order to compare the consistency of the lithium iron phosphate products prepared by the two schemes of Example 5 and Comparative Example 1. The test results are shown in Tables 2 and 3, respectively; wherein SSL501~SSL510 represent the sample numbers selected based on the preparation method of Example 5, and SY01~SY10 represent the sample numbers selected based on the preparation method of Comparative Example 1.
[0127] Table 2 Battery continuous batch performance test corresponding to Example 5
[0128] Table 3 Comparative Example 1 corresponding to the battery continuous batch performance test
[0129] By comparing Table 2 with Table 3, it can be found that the lithium iron phosphate prepared in Example 5 has a lower carbon content but a higher compaction degree than the sample in Comparative Example 1, and in multiple batches of continuous production, the carbon content remains stable and the compaction degree fluctuates less. On the contrary, although the carbon content of the sample in Comparative Example 1 is higher, its carbon content fluctuates more, and the compaction degree is closely related to the change of the carbon content, indicating that the carbon-coated lithium iron phosphate prepared using the organic polymer carbon source of the present invention performs better in terms of stability.
[0130] On the other hand, according to the electrical performance data of 0.1C and 1C in Comparison Table 2 and Table 3, the electrical performance of the two is close at 0.1C, but when discharged at 1C, the charge and discharge efficiency of the sample prepared in Example 5 is significantly higher than that of the sample prepared in Comparative Example 1. At the same time, whether under 0.1C or 1C conditions, the charge and discharge efficiency of the sample prepared in Example 5 is good, which shows that the carbon-coated lithium iron phosphate prepared using an organic polymer carbon source not only has a more uniform coated carbon layer, but also has better stability in carbon content and compaction in the finished product, thereby giving the material more stable electrical properties and high consistency, and the charge and discharge amounts show a high linear correlation, reflecting excellent consistency performance.
[0131] Furthermore, in order to explore the reasons for the above performance differences between the above embodiments and the comparative examples, the morphological states of the samples prepared in Embodiment 4 and the samples prepared in Comparative Example 1 were characterized.
[0132] Figure 1 The infrared spectrum of the organic polymer carbon source prepared in Example 4 is as follows: Figure 1 It can be seen that in infrared spectrum analysis, 3450.98cm -1 There is a broad peak nearby, which is the stretching vibration peak of the associated hydroxyl group. -1 The peak at is attributed to the stretching vibration of the CH bond. The wave number interval is 1450 cm -1 To 1643.52cm -1 It indicates the bending vibration characteristics of the CH bond inside the benzene ring. -1 The peak at 1640 cm reveals the stretching vibration of the COC bond, and the absorption characteristics of phosphonic acid are also observed here. -1 To 1680cm -1 Within the range of , the characteristic absorption peak originally representing the existence of double bonds disappeared, which strongly confirmed that each monomer had successfully completed the polymerization reaction.
[0133] Further, Figure 2 This is the SEM image of the sample prepared in Comparative Example 1; Figure 3 The primary particle size distribution diagram of the sample prepared in Comparative Example 1. Figure 2 It can be seen that the sample of comparative example 1 has significant particle agglomeration. Furthermore, the particle size distribution range of the sample prepared in comparative example 1 is wide but the uniformity is poor. In the statistical samples, the maximum particle size is 2.59 μm, the minimum particle size is 0.03 μm, and the average particle size is 0.28 μm. Specifically, refer to Figure 3 Content shown.
[0134] Further, Figure 4 This is the SEM image of the carbon-coated lithium iron phosphate material prepared in Example 5; Figure 5 This is a primary particle size distribution diagram of the carbon-coated lithium iron phosphate material prepared in Example 5. Figure 4 It can be seen that the prepared carbon-coated lithium iron phosphate has no obvious agglomeration phenomenon. At the same time, the primary particles of the carbon-coated lithium iron phosphate prepared in Example 5 are small, the particle size distribution range is narrow, and the uniformity is good. In the statistical sample, the maximum particle size is 0.96 μm, the minimum particle size is 0.01 μm, and the average particle size is 0.24 μm. Specifically, refer to Figure 5 Content shown.
[0135] Therefore, by comparing Tables 1~2 and Figures 2~5 It can be seen that the particle size distribution range of the sample prepared in Comparative Example 1 is wide but the uniformity is poor, and there is a significant particle aggregation phenomenon. This microscopic morphology results in poor performance of the secondary battery prepared at 1C high rate discharge when the sample prepared in Comparative Example 1 is used in a secondary battery. In contrast, the carbon-coated lithium iron phosphate prepared in the embodiment of the present invention has a narrower particle size distribution, better uniformity and no obvious agglomeration phenomenon. Such a microstructure gives it excellent high rate discharge performance.
[0136] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A method for preparing an organic polymer carbon source, characterized in that: The steps include: Mixing alcohol and ether monomers containing unsaturated double bonds with water to obtain a base material; Mixing a benzene ring monomer, a reducing agent and water to obtain a first mixture; mixing a phosphonic acid monomer, a chain transfer agent and water to obtain a second mixture; An initiator, the first mixture, the second mixture and a coupling agent are added to the base material to obtain the organic polymer carbon source through reaction.
2. The method for preparing an organic polymer carbon source according to claim 1, characterized in that: In the step of preparing the base material, the molar ratio of the alcohol or ether monomer containing an unsaturated double bond to water is (2.5-3.5): (0.1-0.3): (10-20); and / or In the step of preparing the first mixture, the molar ratio of the benzene ring monomer, the reducing agent and water is (0.05-0.40): (0.001-0.005): (5-10); and / or In the step of preparing the second mixture, the molar ratio of the phosphonic acid monomer, the chain transfer agent and water is (0.01-0.20): (0.01-0.02): (5-10).
3. The method for preparing an organic polymer carbon source according to claim 1, characterized in that: The molar ratio of the benzene ring monomer in the first mixture, the phosphonic acid monomer in the second mixture and the ether monomer in the base material is (0.05-0.50): (0.01-0.20): (0.1-0.3); and / or The molar ratio of the initiator, the benzene ring monomer in the first mixture and the coupling agent is (0.10-0.20): (0.05-0.50): (0.01-0.03).
4. The method for preparing an organic polymer carbon source according to claim 1, characterized in that: The alcohol containing an unsaturated double bond is at least one of 3-butene-1,2-diol and ethylene glycol; and / or The ether monomer is at least one of distyrylphenol polyoxyethylene ether, ethylene glycol monovinyl polyoxyethylene ether, 4-hydroxybutyl vinyl ether, isopentanol polyoxyethylene ether and methyl allyl polyethylene glycol ether; and / or The benzene ring monomer is at least one of distyrylphenol polyoxyethylene ether, styrene, hydroquinone and phenylene glycol; and / or The phosphonic acid monomer is at least one of allylphosphonic acid and vinylidene-1,1-diphosphonic acid; and / or The reducing agent is at least one of vitamin C and citric acid; and / or The chain transfer agent is at least one of mercaptopropionic acid and thioglycolic acid; and / or The initiator is at least one of hydrogen peroxide and vitamin C; and / or The coupling agent is at least one of anilinemethyltrimethoxysilane and azobenzene-3,3-dicarboxylic acid.
5. An organic polymer carbon source, characterized in that The organic polymer carbon source is prepared by the method for preparing the organic polymer carbon source according to any one of claims 1 to 4.
6. A positive electrode material, characterized in that The preparation method of the positive electrode material comprises: mixing iron phosphate, a lithium source, a magnesium source, an organic polymer carbon source and water, and obtaining a lithium iron phosphate positive electrode material through dispersion, drying and sintering, wherein the organic polymer carbon source is the organic polymer carbon source according to claim 5.
7. The positive electrode material according to claim 6, characterized in that The molar ratio of iron phosphate, lithium source, magnesium source and organic polymer carbon source is 1: (0.50~0.54): (0.0034~0.0038): (0.0057~0.0060).
8. The positive electrode material according to claim 6, characterized in that The carbon content is 1.22~1.24%, the average primary particle size is 0.22~0.25μm, and the compacted density is 2.52~2.56g / cm 3 .
9. A positive electrode sheet, characterized in that: Comprising the positive electrode material according to any one of claims 6 to 8.
10. A secondary battery, characterized in that: Including the positive electrode sheet as described in claim 9.
Citation Information
Cited By
Polymer, positive electrode material, preparation method of positive electrode material, raw material composition of positive electrode material, pole piece and battery
CN122427334A